1993
DOI: 10.1021/bi00090a008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the arginine-82 to alanine mutation in bacteriorhodopsin on dark adaptation, proton release, and the photochemical cycle

Abstract: The pH dependence of the rate constant of dark adaptation (thermal isomerization from all-trans- to 13-cis-bR) drastically changes when Arg82 of bacteriorhodopsin is replaced by an alanine. In the wild type (WT) the rate decreases sharply between pH 2.5 and pH 5. In R82A the sharp decrease is shifted to pH > 7. This correlates with the shift in the pK of the purple-to-blue transition from pH 2.6 in the wild type to pH 7.2 in the mutant (in 150 mM KCl). We propose that the same group that controls the purple-to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

34
336
0

Year Published

1995
1995
2005
2005

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 179 publications
(370 citation statements)
references
References 58 publications
34
336
0
Order By: Relevance
“…The effect of the arginine 82 to alanine mutation on dark adaptation, proton release, and photochemical cycle in membrane fragments was analyzed by Balashov et al (21). These authors confirmed the reversed order of proton release and uptake observed in Ref.…”
Section: Kinetics Of Proton Release and Uptakementioning
confidence: 57%
See 1 more Smart Citation
“…The effect of the arginine 82 to alanine mutation on dark adaptation, proton release, and photochemical cycle in membrane fragments was analyzed by Balashov et al (21). These authors confirmed the reversed order of proton release and uptake observed in Ref.…”
Section: Kinetics Of Proton Release and Uptakementioning
confidence: 57%
“…In R82A an accelerated deprotonation of the Schiff base and a reversed order of proton release and uptake, detected with pH indicator dyes in the aqueous solution, were already observed (20,21). Moreover, in R82A the pK a of Asp-85, which controls the purple to blue transition, is increased by about 5 pH units compared with wild type (wt) (22).…”
mentioning
confidence: 95%
“…It has been observed that modification of protein groups in the vicinity of the retinal Schiff base shifts considerably the bR absorption spectrum [69] and affects drastically the rates of both thermally- [70] and photo- [71,72] [75,76,77]. At present, there exist a number of ab initio as well as semi-empirical techniques which try to account for the realistic atomic structure and charge distribution of the environment via explicit incorporation of protein (or solution) point charges in the electronic Hamiltonian of the quantum chemically treated substrate [78,79,80,81,82,83].…”
Section: Quantum Chemistry Of In Situ Retinalmentioning
confidence: 99%
“…It has been observed that modification of protein groups in the vicinity of the retinal Schiff base shifts considerably the bR absorption spectrum [69] and affects drastically the rates of both thermally- [70] and photo- [71,72] activated isomerization processes in bR. The experiments imply that the protein environment plays a crucial role in determining the physico-chemical properties of…”
Section: Quantum Chemistry Of In Situ Retinalmentioning
confidence: 99%
See 1 more Smart Citation